GERAKAN PEMBAHARUAN ISLAM INDONESIA DARI MASA KE MASA: SEBUAH PENGANTAR - Soegijanto Padmo (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2007)
This paper attempts to explore the roles of Islamic social organizations which have been very instrumental in the social and cultural transformations in Indonesia. The birth of Islamic organizations and Islamic leaders cannot be separated from oppression of the colonials which had resulted in poverty and backwardness among the Indonesian people. The exploitation of the colonial rulers as well as the oppression of the feudal authorities had created bad attitudes which were against the values of Islam. This paper also observes the conditions which gave birth to some Islamic social movements and describes how social and cultural environments had forced the Islamic leaders and social organizations to find the way out of the problems by conducting social and cultural reformation. They had been successful and the present reformists should learn from their success.